2019
DOI: 10.1182/blood.2019896175
|View full text |Cite
|
Sign up to set email alerts
|

Shared roles for Scl and Lyl1 in murine platelet production and function

Abstract: The stem cell leukemia (Scl or Tal1) protein forms part of a multimeric transcription factor complex required for normal megakaryopoiesis. However, unlike other members of this complex such as Gata1, Fli1, and Runx1, mutations of Scl have not been observed as a cause of inherited thrombocytopenia. We postulated that functional redundancy with its closely related family member, lymphoblastic leukemia 1 (Lyl1) might explain this observation. To determine whether Lyl1 can substitute for Scl in megakaryopoiesis, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…Recently, Lyl-1 was identified as a regulator of mesoderm cell fate 36 and of the maintenance of primitive erythroid progenitors. 37…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Lyl-1 was identified as a regulator of mesoderm cell fate 36 and of the maintenance of primitive erythroid progenitors. 37…”
Section: Resultsmentioning
confidence: 99%
“…The early expression of Lyl-1 in YS mesoderm (Giroux et al, 2007), where it cannot substitute for the mandatory function of its paralog Tal-1 for the generation of haematopoietic progenitors (Porcher et al, 2017), has already been established (reviewed in (Curtis et al, 2012)). More recently, Lyl-1 was also identified as a regulator of mesoderm cell fate in human induced pluripotent stem cells (iPSC) (Palpant et al, 2017), and its function in the maintenance of primitive erythroid progenitors has been described (Chiu et al, 2019). Parallel to Lyl-1 expression in the earliest wave of MΦ progenitor generation, our RNA-seq data now reveal Lyl-1 as an essential regulator in the specification of YS mesoderm to a haematopoietic fate since its invalidation affects major sets of genes involved in embryo patterning.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, disruption of LYL1 activity in mice impairs the long‐term hematopoietic reconstitution capacity and maintenance of early T lineage progenitors, and partially blocks B lymphocyte differentiation 17,18 . More recently, Chiu et al demonstrated that Lyl1 can maintain primitive erythropoiesis and compensate for the loss of Scl (another bHLH family member) in megakaryopoiesis 19,20 . LYL1 is also required for the maturation and stabilization of endothelial adherens junctions in newly formed vessels 16,21 .…”
Section: Introductionmentioning
confidence: 99%
“…17,18 More recently, Chiu et al demonstrated that Lyl1 can maintain primitive erythropoiesis and compensate for the loss of Scl (another bHLH family member) in megakaryopoiesis. 19,20 LYL1 is also required for the maturation and stabilization of endothelial adherens junctions in newly formed vessels. 16,21 Consequently, blood vessels in the lung of young adult Lyl1 −/− mice cannot form a functional endothelial barrier, leading to vascular leakiness.…”
mentioning
confidence: 99%
“…demonstrated that Lyl1 can maintain primitive erythropoiesis and compensate for loss of Scl (a LYL1 co-member of bHLH family) in megakaryopoiesis [19,20]. LYL1 is also required for the maturation and stabilization of endothelial adherens junctions of newly formed vessels [16,21].…”
Section: Introductionmentioning
confidence: 99%